Avaliação de doses da matriz fertilizante MBR no desenvolvimento inicial e na produção de frutas de ameixeira cultivar Irati - Denardi, Tadeu (2012)
Few studies have evaluated organic sources, rock pownders and plants used to cover soil as resources that can provide nutrients to plants. In this context, the aim of this work was to evaluate some doses of matrix MBR fertilizer in the plum culture, cultivar Irati. The work was carried out in the experimental field of Federal Technological University of Paraná – Câmpus Pato Branco from November 2009 to December 2011. The experimental used design was made by chance in blocks with four repetitions and three useful plants by part. Treatments were composed by: one absolute untreated plant (without fertilization), pattern treated plant (complete fertilization 3/3), 2/3 of complete fertilizer associated to 0 kg ha-1 of MBR, 2/3 from complete fertilization associated to 500 kg ha-1 of MBR, 2/3 from complete fertilization associated to 1000 kg ha-1 of MBR and 2/3 from complete fertilization associated to 2000 kg ha-1 of MBR. Quantities of soil nutrients, microbial activity and quantities of nutrients in the leaf plant were analyzed and evaluated. The obtained results from the chemistry soil analysis have shown that: a) quantities of potassium did not change meaningfully which puts in evidence the fertilizer positive effect, probably due to lower leaching process; and b) quantities of phosphorus did not suffer changes, meanwhile it was possible to observe a positive effect and this effect can be associated to the silicon capacity to compete with phosphorus by the same linking sites and consequently to reduce phosphorous adsorption. Microbial activity was not positively or negatively influenced by the use of the matrix fertilizers. Quantities of nutrients in the leaves also did not suffer meaningful changes, with emphasis to quantities of potassium which maintained their own level. In relation to the harvest and post-harvest analyses, it was not noted meaningful changes and the same results were obtained to the production and development analyses of the plants. In general, the updating results indicate a no potential use of fertilizer matrix MBR in the reduction of 1/3 of phosphorous fertilization in the plum culture Irati.